STRATEGIES FOR IMPROVING THE QUALITY OF PUBLIC SERVICES BASED ON SWOT ANALYSIS: A Study on the Application of "Digital Pawnshop" Applications in PT PEGADAIAN (Persero) at Cp Dinoyotangsi Surabaya City - Pujunayu, Zheila Sena (MAP Observer: Jurnal Penelitian Administrasi Publik, 2022)
This study aims to determine the extent of the strategy in the development of Pegadaian Digital to face increasingly fierce competition. In this modern era, many companies are utilizing digital-based services, Pegadaian Digital is a service that is launched without limited space and time. In implementing digital services from PT. Pegadaian (Persero), the kind of analysis that used to find out strategies and procedures for implementing digital services for the community is SWOT analysis in order to find out the Strength, Weakness, Opportunities and Threats that exist in this Pegadaian Digital, the techniques are carried out through qualitative observation in order to collect data and information, qualitative documents and interviews with the source. Determination of informants is carried out by purposive technique, namely determining the first informant who is considered to know more about the development of Pegadaian Digital and is enhanced with the Snowball technique to increase the credibility of the data obtained from the first informant.